A novel approach for exploring the trade-offs between several features of students’ well-being - González-Gallardo, Sandra; Henriques, Carla Oliveira; Marcenaro-Gutiérrez, Óscar David; Luque-Gallego, Mariano (Wiley, 2021)
We propose a novel approach to explore the trade-offs between four features of students’ well-being (anxiety, motivation, sense of belonging, and bullying). On the one hand, a multiobjective interval problem is formulated by considering these distinct components of well-being as objective functions, being then instantiated with confidence intervals obtained from distinct econometric estimations. Then, the problem is solved through the use of a reference point approach that allows accounting for the decision maker's preferences by considering a set of weight vectors that can be used to express his/her preferences regarding the importance that should be given to each objective function. The results provide information on how the improvement of one objective might affect the remaining objectives. Furthermore, the student's profile corresponding to each scrutinized solution is also made available. Overall, the results claim that bullying is the most affected objective, highlighting the need to foster antibullying education policies in Spanish schools, according to PISA 2015 data. Finally, some educational polices are suggested in order to enhance students’ well-being.
Keywords: Econometría; Econometric analysis; Interval programming; Multiple objective programming; Students’ well-being